ANALYSIS OF INTERPRETATION ON THE BANNER OF LAMONGAN PECEL LELE - Heri Iswandi; Husni Mubarat (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2019)
Life goes on with the obtained experience. Human’s life depends on nature and its surrounding environment, including artworks made by human. Art experience is an experience obtained by human like the daily experience so art experience is also an intact experience involving feeling, mind, sense, and various human intuitions. The banner of Lamongan pecel lele is an art instrument existing from human’s interpretation based on s/he experience when s/he understands and reprocesses an object. Starting from what’s observed, the writer tried to analyze and reveal the meaning of visual form drawn on that banner. Visual dissection drawn on that banner was conducted in detail. It aims at receiving result that’s more than the meaning obtained based on people’s perception and writer’s one. In other words, pecel lele banner is not only interpreted as what it’s used for (merit value) pecel lele seller but it’s also to see and perceive banner drawing based on the variant of food product sold. However, there is another meaning that has been hidden this long and hasn’t been known by people yet.